Sentiment Analysis of Halal Media and Recreation Trends in The Last 10 Years - Siti Maysyaroh; Siti Salmah; Tri Nadia (SMART Insight, 2022)
This research aims to examine trends in halal media and recreation in the last ten years globally and is reviewed from scientific studies in the journal published Dimension. This research uses the sentiment analysis method from secondary data in 106 papers published in the last ten years, namely 2013 to 2023, then processed using Microsoft Excel 2019 and SentiStrengh. The research results illustrate that the analysis of good (positive) sentiment is 45.3%, bad (negative) sentiment is 21.7%, and the rest has a neutral sentiment of 33%. The results of this discovery with sentiment analysis found that halal media and recreation trends in the last ten years tend to have positive sentiments. From the results of this analysis, both positive, negative, and neutral sentiments are challenges and opportunities for interested parties, including the government, academics, and so on, to provide a strong understanding regarding halal media and recreation.